Effect of different rice planting methods on the water, energy and carbon footprints of subsequent wheat - Jin, Zhaoqiang; Mu, Yixue; Li, Yusheng; Nie, Lixiao (Frontiers in Sustainable Food Systems, 2023)
The rice-wheat rotation system is an important planting system in the middle and lower reaches of the Yangtze River. Studies on the effects of different rice planting methods on the water, energy, and carbon footprints of subsequent wheat have rarely been reported. In this study, the effects of different rice cultivation practices on the water, energy, and carbon footprints of subsequent wheat were investigated among different rice-wheat rotation systems including dry direct-seeded rice (DSR)-wheat rotation, wet direct-seeded rice (WSR)-wheat rotation and transplanted rice(TPR)-wheat rotation. Results showed that the yield of wheat after DSR was 8,552 kg ha−1, which was 14.61 and 4.72% higher than the yields after WSR and TPR, respectively. In addition, the water and carbon footprints of wheat after DSR were lower than those after WSR and TPR, while its energy and carbon production efficiencies and net ecosystem economic benefits were higher than those after WSR and TPR. Notably, the use of fertilizers and fuel are the two major contributors to the high energy inputs and greenhouse gas emissions in wheat production. In summary, wheat after DSR has higher ecological and economic benefits, and we recommend that it be promoted as the preferred wheat planting model in rice-wheat rotation areas.